Challenges in Talent Retention Amid adopting new manufacturing practices in the Automobile sector of Chennai. (Journal of Informatics Education and Research, 2025)
The Automobile industry is expected to grow by 270 Billion USD by 2028 and it will contribute the employment opportunities for 65 million people. Chennai is known as the “Detroit of Asia” and the “automobile capital of India.While considering the growth of the sector, immediate attention is essential in retaining its employees. Hence an attempt was made to study about the challenges faced by the employers and employees amid organizational changes in automobile sector. The total number of respondents is 400. The convenient sampling techniques was adopted and both primary and secondary data were utilised. The questionnaire was circulated to collect the primary data. One way ANOVA and Regression analysis were applied in this study.